Constructing Cultural Bridges: The Role of Midamar Corporation’s Halal Discourse in Muslim-Western Social Integration - Kurnia, Sendi; Ulinnuha, Roma (Cakrawala: Jurnal Studi Islam, 2024)
Social integration between Muslim and Western societies reflects complex dynamics in intercultural relations involving two historically, culturally, and religiously distinct social realities. Various issues arise in the integration process between Muslim and Western societies, one of which is halal food labeling. This research examines how the halal discourse, particularly in the case of Midamar Corporation, shapes shared consciousness and influences social interactions between the two groups. Employing a qualitative approach, this study reveals that Midamar Corporation, as a key actor, plays a significant role in shaping the understanding of halal products and mediates the relationship between Muslim identity and consumption. The research findings indicate that the halal discourse is not merely a product label, but also a means of constructing identity and a space for negotiating meanings in a global context.